"The effects of family therapeutic interventions on mental health and quality of life of children with cancer: A systematic review". (July 2022) - Vasilopoulou, Konstantina; Skoutari, Angeliki; Siomos, Konstantinos; Christodoulou, Nikolaos
Background: The diagnosis of a childhood malignancy and the following period are very stressful for the little patient and the whole family. Depression, anxiety, and poor quality of life (QoL) are some of the negative effects of pediatric cancer to the children and their parents. Family therapeutic interventions aim to improve mental health and QoL of these children. Methods: A systematic search of the electronic database PubMed was conducted for articles that studied the effect of family therapeutic interventions on mental health and QoL of children with cancer. Results: A total of 634 articles were evaluated, of which 10 articles met the inclusion criteria. A percentage of 70% of the studies, representing seven different types of interventions, seemed to be beneficial for the participant's mental health and QoL. The remaining three studies did not significantly improve mental health and QoL. Conclusion: The results of our review indicate that family psychosocial interventions are beneficial for children with cancer. These children and their families are a growing population requiring more patient-centered, time flexible interventions which may enhance family bonding and patients' positive emotions.